Assessing the Association Between E-Cigarette Use and Exposure to Social Media in College Students: A Cross-Sectional Study. (6th December 2017) - Sawdey, Michael D.; Hancock, Linda; Messner, Marcus; Prom-Wormley, Elizabeth C.
ABSTRACT: Background: Social media platforms provide an indirect medium for encouraging e-cigarette use between individuals and also serve as a direct marketing tool from e-cigarette brands to potential users. E-cigarette users share information via social media that often contains product details or health-related claims. Objective: Determine whether e-cigarette use is associated with exposure to e-cigarettes on social media in college students. Methods: Data from a sample of 258 college students was obtained via a clicker-response questionnaire (90% response rate). Demographic, lifetime and current e-cigarette/cigarette use, and e-cigarette exposure via social media (peer posts or advertisements) were examined. Logistic regression was used to assess the relationship between lifetime and current e-cigarette use and viewing peer posts or advertisements on social media while adjusting for cigarette use and self-posting about e-cigarettes. Results: Overall, 46% of participants reported lifetime e-cigarette use, 16% current e-cigarette use, and 7% were current dual users of e-cigarettes and cigarettes. There were positive and significant associations between lifetime e-cigarette use and viewing peer posts (aOR = 3.11; 95% CI = 1.25–7.76) as well as advertisements (aOR = 3.01; 95% CI = 1.19–7.65) on e-cigarettes via social media after adjusting for cigarette use. Current e-cigarette use was only significantly associated with viewing peer posts via social media (aOR = 7.58; 95% CI = 1.66–34.6) after adjusting for cigarette use. Conclusions/Importance: Almost half of college students view peer posts and advertisements on e-cigarettes via social media. This exposure is associated with individual e-cigarette use. Continued efforts to examine online e-cigarette content are needed to help future interventions decrease e-cigarette use.